Outcomes of patients with diffuse large B-cell and high-grade B-cell lymphomas with synchronous CNS and systemic involvement at diagnosis treated with high-dose methotrexate and R-CHOP: a single-center retrospective study. (July 2022) - Fleming, Megan; Huang, Ying; Dotson, Emily; Bond, David A.; Reneau, John; Epperla, Narendranath; Alinari, Lapo; Brammer, Jonathan; Christian, Beth; Baiocchi, Robert A.; Maddocks, Kami; Sawalha, Yazeed
Background: The optimal treatment of patients with systemic diffuse large B-cell (DLBCL) or high-grade B-cell (HGBL) lymphomas with synchronous central nervous system (CNS) involvement at diagnosis is not well defined. High-dose methotrexate administered concurrently with R-CHOP (RM-CHOP) is a commonly used regimen, but data on outcomes achieved with this regimen are limited. Objective: To report our experience with RM-CHOP in patients with systemic DLBCL or HGBL with synchronous CNS involvement at diagnosis. Design: A single-center retrospective analysis. Methods: We identified consecutive patients with systemic DLBCL or HGBL with synchronous CNS involvement at diagnosis who were treated with RM-CHOP from January 2012 to January 2021. Results: Fifty patients were included with a median age of 62 years; 82% had DLBCL ( n = 41) and 18% had HGBL ( n = 9). Treatment with RM-CHOP was followed by consolidative autologous hematopoietic cell transplantation in 14 patients (28%). The complete response (CR) rate following RM-CHOP was 62%. With a median follow-up of 40 months, the median progression-free (PFS) and overall (OS) survivals were 16 and 58 months, and the 2-year PFS and OS were 41% and 57%, respectively. The 2-year cumulative incidence of CNS progression/relapse was 29%. Outcomes were particularly poor in HGBL, with median PFS and OS of 6 and 7 months, compared with median PFS and OS of 22 months and not reached in DLBCL, respectively. The outcomes of patients with relapsed/progressive disease were poor, with only 63% of patients receiving subsequent treatments and only 21% achieving CR to next subsequent treatment. Most patients (58%) with disease relapse/progression had CNS involvement which was associated with very poor outcomes (median OS of 2 months). Conclusion: CNS involvement in aggressive B-cell non-Hodgkin lymphoma at diagnosis dictates clinical outcomes and requires more effective treatment options.